Pembangunan Aplikasi Berbasis Android sebagai Penyedia Informasi Klub Futsal di Bekasi - Ivan Setyanto; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to build an application as an information provider for amateur futsal clubs for ages 12-17 years old in Bekasi, West Java. The method used in application development is the Prototyping Method which consists of five stages, namely Communication, Quick Plan, Modeling Design, Constructions and Deployment delivery. The software analysis modeling uses the Unified Modeling Language (UML). The Android-based application running with minimum system required Android 5.0 or above. The result of this study is an Android-based application as a provider of information for amateur futsal clubs aged 12- 17 years in Bekasi named